The NFL-225 test as a measure of bench press strength in college football players - Mayhew, J. L.; Ware, J. S.; Bemben, M. G.; Farris, B.; Wilt, B.; Ward, T. E.; Slovak, J. P.; Juraszek, J. (The Journal of Strength and Conditioning Research, 1999)
To assess the efficacy of the NFL-225 test to evaluate upper-body strength in football players, 142 college players (69 Division IAA and 73 Division II) were measured at the conclusion of their off-season resistance training program for 1 repetition maximum (1 RM) bench press and repetitions to fatigue with 225 lb. A validation sample of players (n = 114) was randomly selected to develop a prediction equation that was significantly correlated with 1 RM (r = 0.96) and allowed reasonably accurate predictions (SEE = 14.1 lb). The remaining 28 players served as a cross-validation sample that produced a high correlation (r = 0.96) and a nonsignificant difference (t = 0.46) between predicted and actual 1 RM. Sixty-eight percent of the cross-validation sample had predicted 1 RM values within ±10 lb of their actual 1 RM performance. Therefore, muscular endurance repetitions with an absolute load of 225 lb can be used to predict 1 RM bench press strength in college football players, although the error in prediction increases when endurance performance exceeds 10 repetitions.